2006
DOI: 10.1002/dev.20176
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of early olfactory experience on later olfactory conditioning

Abstract: This study examined the duration of the effect of early olfactory experience in rats by determining the ease of conditioning and then reconditioning to an early-experienced odor. Rat pups (experimental group) were exposed to aniseed odor sprayed on the mother's belly from day 1 to 20 after birth. A control group was exposed only to water. At the ages of 21 and 40 days all the rats (experimental and control) were tested for preference for the odor of aniseed. Starting from day 41 after birth they were condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In infancy, this odor blocks fear conditioning and prevents amygdala plasticity in older pups by blocking the release of the stress hormone corticosterone (Moriceau and Sullivan, 2006; Shionoya et al, 2007; Stanton and Levine, 1990; Wiedenmayer et al, 2003), which prevents infant amygdala plasticity (Moriceau and Sullivan, 2006; Moriceau et al, 2006). Furthermore, this safety signal appears to be retained into adulthood as indicated by the natural and learned maternal odors' abilities to enhance sexual (Fillion and Blass, 1986; Mainardi et al, 1965; Marr and Gardner, 1965; Moore et al, 1996) and maternal behaviors (Shah et al, 2002), improve olfactory discrimination learning (Blais et al, 2006), reduce conditioned odor aversion (Sevelinges et al, 2009a,b) and reduce fear learning and amygdala activity (Sevelinges et al, 2007; Sevelinges et al, 2008). The present data suggest this odor also reduces depressive-like behavior, which is also consistent with the notion of a safety signal (Pollak et al, 2008; Rogan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In infancy, this odor blocks fear conditioning and prevents amygdala plasticity in older pups by blocking the release of the stress hormone corticosterone (Moriceau and Sullivan, 2006; Shionoya et al, 2007; Stanton and Levine, 1990; Wiedenmayer et al, 2003), which prevents infant amygdala plasticity (Moriceau and Sullivan, 2006; Moriceau et al, 2006). Furthermore, this safety signal appears to be retained into adulthood as indicated by the natural and learned maternal odors' abilities to enhance sexual (Fillion and Blass, 1986; Mainardi et al, 1965; Marr and Gardner, 1965; Moore et al, 1996) and maternal behaviors (Shah et al, 2002), improve olfactory discrimination learning (Blais et al, 2006), reduce conditioned odor aversion (Sevelinges et al, 2009a,b) and reduce fear learning and amygdala activity (Sevelinges et al, 2007; Sevelinges et al, 2008). The present data suggest this odor also reduces depressive-like behavior, which is also consistent with the notion of a safety signal (Pollak et al, 2008; Rogan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several works also reported that early learned preferences modulate adult learning processes. Rat pups exposed to artificial odor sprayed on the mother's belly from birth to weaning at postnatal day (PN) 20 exhibited facilitation of olfactory discrimination learning with this odor at adulthood (Blais, Terkel, & Goldblatt, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the benefit of territoriality, individual recognition by familiarisation may allow reducing the intensity of agonistic encounters. The importance of experience acquired during the first encounters can be determining in mechanisms of kin recognition [34][35][36], and Taylor and Irwin [37] showed that altruism might be promoted by overlapping generations. Erhart et al [38] suggested that social learning and social history are the most likely mechanisms for kin recognition.…”
Section: Discussionmentioning
confidence: 99%